Prognostic significance of TET2 mutations in myelodysplastic syndromes: A meta-analysis. (July 2017) - Guo, Zhen; Zhang, Shao-kai; Zou, Zhe; Fan, Rui-hua; Lyu, Xiao-dong
Highlights: TET2 mutations occur frequently in MDS and its prognostic impact has not been fully assessed and was controversial. A meta-analysis was used to evaluate the prognostic significance of TET2 mutations in MDS. Our results suggest TET2 mutations may not impact prognosis on OS of patients with MDS. Abstract: Tet methylcytosine dioxygenase 2 (TET2) mutations occur frequently in myelodysplastic syndromes (MDS), but its prognostic impact has not been fully assessed and was controversial. Therefore, we performed a meta-analysis to evaluate the prognostic significance of TET2 mutations in MDS. PubMed, EMBASE databases and Cochrane Library were searched for studies reporting TET2 mutations and overall survival in MDS. Hazard ratios (HR) with 95% confidence interval (CI) were determined using random-effect modeling. A total of 1494 patients from nine studies were subjected to meta-analysis. The frequency of TET2 mutations was 18.34% (274/1494) in the study. MDS with TET2 mutations had similar overall survival compared to patients without the mutations (hazard ratio 1.13, 95% CI: 0.81–1.5).Our findings suggest that TET2 mutations have no prognosis impact on OS of patients with MDS. Therefore, the status of TET2 mutations cannot be served as a prognostic marker in MDS.